034 Early lowering of blood pressure after acute intracerebral haemorrhage: systematic review and meta-analysis of patient-level data. Issue 6 (27th May 2022) - Moullaali, Tom; Wang, Xia; Sandset, Else; Woodhouse, Lisa; Law, Zhe Kang; Salman, Rustam Al-Shahi; Anderson, Craig; Bath, Philip
Abstract : Objective: To summarise evidence of the effects of blood pressure (BP)-lowering interventions after acute spontaneous intracerebral haemorrhage (ICH). Methods: Pre-specified systematic review of the Cochrane Central Register of Controlled Trials, EMBASE and MEDLINE databases from inception to 23 June 2020 to identify randomised controlled trials that compared active BP-lowering agents vs. placebo or intensive vs. guideline BP-lowering targets for adults <7 days after ICH. Primary outcome was function (distribution of scores on the modified Rankin scale) 90 days after ran- domisation. Radiological outcomes were absolute (>6mL) and proportional (>33%) haematoma growth at 24 hours. Meta-analysis used a one-stage approach, adjusted for pre-specified covariables and trial. Results: Of 7094 studies identified, 50 trials involving 11, 494 patients were eligible and 16 (32.0%) shared patient-level data from 6, 221 (54.1%) patients (mean age 64.2 [SD 12.9], 2, 266 [36.4%] females) with a median time from symptom onset to randomisation of 3.8 hours (IQR 2.6−5.3). Active/intensive BP-lowering had no effect on the primary outcome compared to placebo/guideline treatment (adjusted OR for unfavourable shift in modified Rankin scale scores: 0.97, 95%CI 0.88−1.06; p=0.50), but there was signifi- cant heterogeneity by strategy (pinteraction=0.031) and agent (pinteraction<0.0001). Active/intensive BP-lowering reduced absolute and relative haematoma growth. Interpretation: Overall, a broad range of interventions to lower BP within 7 days of ICH had no benefit on functional recovery, despite reducing bleeding. The treatment effect appeared to vary according to strategy and agent. tom.moullaali@ed.ac.uk